Development of Mesoporous Geo-Adsorbent Pellets from Low Fire Clay and Cellulose for Removal of Methylene Blue in Aquaculture - Sharma, Priyanka; Qanungo, Kushal (Asian Journal of Chemistry, 2021)
Porous ceramic pellets have been prepared using low fire clay and cellulose as a pore forming agent. The pore size and BET analysis, water absorption capacity and compressive strength of the pellets have been determined. The methylene blue uptake of pellets increased on increasing the percentage of initial cellulose content. Batch mode studies showed that the methylene blue adsorption decreased with increasing dose of pellets, increased with increasing initial dye concentration, while solution pH and presence of co-ions had negligible effect on removal of methylene blue, making them suitable for dye removal over a wide range of pH. The adsorption process followed both the Freundlich and Langmuir adsorption isotherms, whereas the adsorption kinetics followed the pseudo-second-order kinetic model. An inexpensive and simple device consisting of the mesoporous pellets enclosed in a tea ball wire mesh, which can be conveniently dipped and taken out of water in an aquarium and can remove methylene blue, has been developed.